(untitled) - Ashenden, Peter J. (London, 2002)
"The second edition of The Designer's Guide to VHDL sets a new standard in VHDL texts. I am certain that you will find it a very valuable addition to your library."
Keywords: VHDL (Computer hardware description language),Electronic digital computers,Ngôn ngữ mô phỏng phần cứng máy tính,Máy tính điện tử kỹ thuật số; Computer simulation,Sự mô phỏng máy tính